Rapid response teams in the Eastern Mediterranean Region: Results from the baseline survey of country-level capacities, operations and outbreak response capabilities - Sherein Elnosserry; Evans Buliva; Amgad Abdalla Elkholy; Amira Mahboob; Shaffi Fazaludeen Koya; Abdinasir Abubakar (Taylor & Francis Group, 2024)
ABSTRACTThe aim of this study is to assess WHO/Eastern Mediterranean region (WHO/EMR) countries capacities, operations and outbreak response capabilities. Cross-sectional study was conducted targeting 22 WHO/EMR countries from May to June 2021. The survey covers 8 domains related to 15 milstones and key performance indicators (KPIs) for RRT. Responses were received from 14 countries. RRTs are adequately organised in 9 countries (64.3%). The mean retention rate of RRT members was 85.5% ± 22.6. Eight countries (57.1%) reported having standard operating procedures, but only three countries (21.4%) reported an established mechanism of operational fund allocation. In the last 6 months, 10,462 (81.9%) alerts were verified during the first 24 h. Outbreak response was completed by the submission of final RRT response reports in 75% of analysed outbreaks. Risk Communication and Community Engagement (RCCE) activities were part of the interventional response in 59.5% of recent outbreaks. Four countries (28.6%) reported an adequate system to assess RRTs operations. The baseline data highlights four areas to focus on: developing and maintaining the multidisciplinary nature of RRTs through training, adequate financing and timely release of funds, capacity and system building for implementing interventions, for instance, RCCE, and establishing national monitoring and evaluation systems for outbreak response.